Work Stress Level and Caring Behaviour of Nurses - Retno Lestari; Kumboyono Kumboyono; Luthfia Dyta (Jurnal Ners, 2010)
Introduction: A nurse who experience burnout feelings will influence their motivation, and quality performance. This situation is probably affecting a decline in work quality towards the caring behaviour demonstrated by nurses to their patiens, particularly for a nurse who are working in the long-stay installation room facing directly to patient's problems. The purpose of this research is to identify the work stress level of nurse towards the nurse's caring behaviour in the long-stay installation room (IRNA) in general hospital in Malang.Method: This research used descriptive – correlational, the sampling was Non Probability Purposive Sampling with 93 nurses as the corresponds. The data was analyzed by operating Correlation Pearson, with a significance of p < 0.05.Result: The result found that there was a substantial correlation between the work stress level and the nurse's caring behaviour with p = 0.008 and r = -0.274, and it was a negative correlation.Discussion: It means that when the stress level of nurses will declined, the nurse's caring behavior automatically will beamplified. Conversely, if the stess level of nurses intensively increased, the nurse's caring behaviour become decreased. Thus, this research is needed to be analyzed further in order to asses the quality of caring behaviour by expanding the connected indicator and variable. It is aimed to improve the professionalism and quality of nurses in giving the best service to patients this research need to be continued further in order to asses the quality of nurse's caring behavior by expanding the variable, which is related to internal factors, such as knowledge, perception, emotion, ect and also connected to external factors, such as environment, both physically and non physically like: climate, human being, social economic, culture and ect.